THE PRODUCTION OF BREADFRUIT FLOUR: EFFECT OF HEATER TEMPERATURE TO THE DRYING RATE AND TIME OF THE BREADFRUIT - Sari, Denni Kartika; Lestari, Retno Sulistyo Dhamar (Universitas Negeri Semarang, 2017)
The composition of mineral and vitamin from breadfruit is particularly known of having benefits compared to rice which is a main source of carbohydrate consumed by societies. The process of drying is one of the factors that affects foodstuffs quality. The aim of this research was to provide an understanding of drying phenomena from data experiment and discover the influence of drying air temperature to breadfruit drying time and rates. This research was conducted in several stages which are material preparation (breadfruit) by through downsizing process, then weigh the material (breadfruit) once every 5 minutes on each drying air Â temperature variations (50 ÂºC, 60 oC, 70 oC, and 80 oC). The research were conducted using breadfruit with the best drying time which is obtained at 60 0C for 100 minutes. The lowest water content obtained was 0.4%, while the highest drying rate was 0.00144 Kg2/m2.s at 80 ÂºC of temperature.